An alternative explanation for the variation in reported estimates of risk aversion - Denis Conniffe; Donal O'Neill (Institute for the Study of Labor (IZA), 2012)
There is a large literature estimating Arrow-Pratt coefficients of absolute and relative risk aversion. A striking feature of this literature is the very wide variation in the reported estimates of the coefficients. While there are often legitimate reasons for these differences in the estimates, there is another source of variation that has not been considered to date. The Arrow-Pratt coefficients are properties of the utility functions, but a number of estimates are obtained by equating these to risk aversion measures defined in a mean-variance framework. This paper shows that while the legitimacy of the mean-variance approach may hold under general conditions the additional assumptions invoked when estimating the risk aversion parameter hold only in very restricted circumstances and that serious under or over estimation can easily arise as a result.
Keywords: C91; D81; G11; 330; variability in risk aversion estimation; mean-variance estimation; location scale; Risikoaversion; Schätztheorie; Theorie